Updated Perspectives on the Management of Sleep Disorders in the Intensive Care Unit - Nilius G (Dove Medical Press, 2021)
Georg Nilius,1,2 Matthias Richter,1 Maik Schroeder1 1Kliniken Essen Mitte, Department of Pneumology, Essen, Germany; 2Witten/Herdecke University, Department of Internal Medicine, Witten, GermanyCorrespondence: Georg NiliusKEM, Evang Kliniken Essen-Mitte gGmbH, Am Deimelsberg 34 a, Essen, 45276, GermanyEmail g.nilius@kem-med.comAbstract: Sleep disorders and circadian dysrhythmias are extremely prevalent in critically ill patients. Impaired sleep has a variety of etiologies, exhibits a wide range of negative effects and, moreover, might deteriorate the patient’s prognosis. Despite a number of scientific findings and increased awareness, the importance of sleep optimization is still lower on the list of priories in the intensive care unit (ICU). The techniques of measuring and the evaluation of sleep quantity and quality are a great challenge in the ICU setting. The subjective and objective tools of sleep validation continue to suffer from deficiencies. Treatment approaches to improve the critically ill patient’s sleep have focused on non-pharmacologic and pharmacologic strategies with some promising results. But pharmacological interventions alone could not provide sufficient patient benefit. Being aware and knowing of sleep problems and the beneficial effect of the necessary therapies in ICU patients requires greater acceptance. The application of available methods and the development of new methods to prevent sleep disorders in the ICU offer the potential to improve the critically ill patient’s outcome.Keywords: ICU, sleep disorders, circadian rhythms